Peningkatan Kemampuan Komunikasi Matematika Siswa SD Kelas V Melalui Tipe Pembelajaran Think Talk Write (TTW) - Novy Trisnani (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Kristen Satya Wacana, 2020)
This study aims to improve the mathematical communication skills of fifth grade students in SD Negeri Kedundang through the application of cooperative learning models of Think Talk Write type. This type of research is classroom action research. The subjects in this study were 19 students. The technique used for data collection is observation and written test techniques. The research instrument is the teacher observation sheets, student observations and written tests. The data analysis technique used is descriptive quantitative and descriptive qualitative. The results of pre-action observation showed that students' communication skills were categorized as very low (47.63%) and low (38.48%). Then in the first cycle, students' mathematical communication skills on average increased from very low and low to low (22.60%), moderate (27.60), and high (22%). To strengthen the results of observations from the first cycle, the learning activities were held in the second cycle, the results of students' mathematical communication skills increased to the medium category (37.36%), high (39.47%), and very high (18.42%). Based on the results obtained it can be concluded that the application of the think talk write learning model can improve the mathematical communication skills of fifth grade students of Kedundang Elementary School.